Basa-Basi dalam Sapaan: Studi Pragmatik terhadap Kesantunan Berkomunikasi Masyarakat Indonesia - Talitha Fashohatul Azmi; Choirun Nisa'; Cindy Effelina Zakkia Putri; Prima Vidya Asteria (Universitas Muhammadiyah Surabaya, 2026)
Small talk in greetings is an integral part of polite communication in Indonesian society, rooted in cultural and social values. This study aims to identify and analyze forms of small talk in Indonesian greetings through Geoffrey Leech’s politeness principles. This research employs a descriptive qualitative approach with a pragmatic discourse analysis method. The data source consists of utterances found in Indonesian-language vlog videos produced by the researchers and uploaded to the Plurikultural Indonesia YouTube channel. Data were collected using observation, participation, and note-taking techniques, and analyzed based on Leech’s politeness maxims: tact, generosity, approbation, modesty, agreement, and sympathy. The findings reveal that small talk expressions in greetings reflect pragmatic strategies to maintain harmony and communication ethics. Each maxim emerges in varied contexts depending on the situation and relationship between speakers. These findings highlight the significance of politeness in daily interaction and have implications for the development of contextual BIPA teaching materials and intercultural education rooted in local values.